Pola Komunikasi Terapeutik Petugas Layanan Rehabilitasi BNNK Purbalingga Pada Klien Rehabilitasi Narkoba: Therapeutic Communication Patterns of Rehabilitation Service Officers at BNNK Purbalingga for Drug Rehabilitation Clients - Sofia, Dwi; Hikam Suyuti, Muh (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
Drug abuse is a very serious issue and requires a rehabilitation approach that prioritizes therapeutic communication. This study aims to analyze the therapeutic communication patterns applied by rehabilitation service officers at BNNK Purbalingga. Using a qualitative approach and descriptive methods, this research involved in-depth interviews and direct observations of the rehabilitation process. The study results show that the officers emphasize empathy-based communication, building trust through a personalized approach, and avoiding confrontation when interacting with clients. They also use assessment techniques to explore clients' backgrounds and implement monitoring strategies such as home visits and video calls to ensure the continuity of recovery. Family involvement is found to play an important role in enhancing the effectiveness of rehabilitation. Through this research, we gain a deeper understanding of the significance of therapeutic communication in shaping supportive relationships that facilitate clients' recovery processes. Furthermore, this study offers a communication model that could be adopted in similar rehabilitation services in other regions.